Awake tracheal intubation using king Vision video laryngoscope in traumatic cervical spine patients: A case series. (August 2022) - Ahmad, Sarfaraz; Sahay, Nishant; Naaz, Shagufta; Singh, Kunal
Abstract: Intubation in patients with cervical spine injury with neurological deficits needing urgent surgery mandates and careful airway management. Video laryngoscopy-guided intubation in an awake patient can be a useful option as the patient can himself participate in the airway management. The patient can follow commands, protrude the tongue, and indicate discomfort or pain during inadvertent or excessive head extension. We wish to report our experience of 10 patients with documented neurological compromise needing urgent surgery after cervical spine trauma where we used the King Vision video laryngoscope for awake tracheal intubation. Nine out of 10 patients were successfully intubated with the King Vision but we could not intubate one patient for which fibreoptic bronchoscope-guided intubation was performed. Three patient needed gum elastic bougie assistance for intubation. The mean time for intubation ranged from 1.2 minutes to 2.6 minutes. Pain and discomfort during the intubation attempt were noted to be acceptable.